2016
DOI: 10.1093/nar/gkw391
|View full text |Cite
|
Sign up to set email alerts
|

Use of chemical modification and mass spectrometry to identify substrate-contacting sites in proteinaceous RNase P, a tRNA processing enzyme

Abstract: Among all enzymes in nature, RNase P is unique in that it can use either an RNA- or a protein-based active site for its function: catalyzing cleavage of the 5′-leader from precursor tRNAs (pre-tRNAs). The well-studied catalytic RNase P RNA uses a specificity module to recognize the pre-tRNA and a catalytic module to perform cleavage. Similarly, the recently discovered proteinaceous RNase P (PRORP) possesses two domains – pentatricopeptide repeat (PPR) and metallonuclease (NYN) – that are present in some other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…This is probably because the mutation at position 35 introduces a negative charge that can interfere with RNA binding. Still, although PPR1 mutant does not display a loss of RNase P activity, our data suggest that the PPR1 motif is in the vicinity of the RNA in accordance with previous work showing contacts between the N-terminal extremity of PRORP and tRNA (28). In contrast, PPR motifs 4 and 5 do not seem to be involved in RNA interaction because their mutations do not alter RNA binding and cleavage.…”
Section: Biophysical Analysis Of Prorp2-trna Complexsupporting
confidence: 90%
“…This is probably because the mutation at position 35 introduces a negative charge that can interfere with RNA binding. Still, although PPR1 mutant does not display a loss of RNase P activity, our data suggest that the PPR1 motif is in the vicinity of the RNA in accordance with previous work showing contacts between the N-terminal extremity of PRORP and tRNA (28). In contrast, PPR motifs 4 and 5 do not seem to be involved in RNA interaction because their mutations do not alter RNA binding and cleavage.…”
Section: Biophysical Analysis Of Prorp2-trna Complexsupporting
confidence: 90%
“…Results thus represent indirect evidence to show the importance of the PPR domain for RNA recognition and do not conclusively show if and/or how PPR motifs confer specificity to PRORP enzymes. In another study, lysine residues positioned at both tips of PRORP Λ shape were found in contact with the pre-tRNA substrate [ 59 ], thus, in agreement with the general substrate binding process proposed for PRORP proteins [ 5 ]. Mutated residues that were shown to interact with pre-tRNA and/or to be essential for RNase P activity are shown in Figure 2 .…”
Section: Mechanistic Analyses Of Protein-only Rnase P Activitysupporting
confidence: 77%
“…[4, 19] DNA templates containing a class III Φ6.5 promoter and the genes for either MR1 or MR2 model RNAs were generated using a pair of DNA oligonucleotides for each RNA (Table S2; Sigma). These oligonucleotides were designed to be complementary at their respective 3’-termini; the 17-bp complement allowed fill-in with Phusion DNA Polymerase (NEB).…”
Section: Methodsmentioning
confidence: 99%